Alcohol, smoking and rectal cancer risk in a Mediterranean cohort of adults: the European Prospective Investigation into Cancer and Nutrition (EPIC)-Italy cohort. Issue 4 (April 2020) - Bendinelli, Benedetta; Palli, Domenico; Assedi, Melania; Facchini, Luigi; Grioni, Sara; Agnoli, Claudia; Ricceri, Fulvio; Macciotta, Alessandra; Panico, Salvatore; Mattiello, Amalia; Tumino, Rosario; Giurdanella, Maria C.; et al.
Abstract : Objective: Colorectal cancer (CRC) is one of the most diagnosed malignant cancers worldwide. Rectal cancers (Rcs) represent one-third of all CRCs. Cigarette smoking and alcohol drinking are two underestimated risk factors for RC. We aimed to evaluate the role of alcohol consumption and cigarette smoking in modulating RC risk and to estimate the attributable fraction in a Mediterranean population. Methods: In the Italian section of the European Prospective Investigation into Cancer and Nutrition, 45, 553 healthy adults (31, 252 women) were recruited and provided information about lifestyle and dietary habits. During 14.0 years of median follow-up, 154 incident RC cases were identified. Results: In multivariate models, a increase in RC risk emerged among subjects drinking more than 3 drinks/day, overall (hazard ratio [HR] = 1.74; 95% confidence interval [CI] 1.08–2.80), and in females (HR= 2.80; 95% CI 1.23–6.35), compared with drinkers of less than 1 drink/day. A increase in risk also emerged for current- compared with never-smokers, overall (HR = 1.57; 95% CI 1.06–2.35; P for trend 0.03) and among males (HR = 2.04; 95% CI 1.02–4.07; P for trend 0.045). Overall, 9% (95% CI 4–14%) of RC cases were attributable to drinking more than 3 drinks/day and 12% (95% CI 3–19%) were attributable to current smoke and 20% (95% CI 11–27%) of RC cases were attributable to the independent effects of these two exposures. Conclusion: Our study supports a strategy to avoid a relevant proportion of rectal cancer cases through a combined reduction of alcohol consumption and cigarette smoking. Abstract : Supplemental Digital Content is available in the text.